University teaching as a profession for women in Oxford, Cambridge and London, 1870-1930 - Perrone, FH (1991)
This thesis is an account of how an academic profession for women evolved in England during the period 1870 to 1930. While a great deal of work has been done from a feminist perspective on the education of girls, higher education has been less frequently examined, especially from the point of view of the academic staff. Studies of women's higher education have tended to concentrate on the women's colleges, and how they provided an alternative to the traditional family for single women. While this approach is valuable, it is also necessary to place women academics within the context of the development of an academic profession in which both men and women participated. Academic careers for women can be seen in connection with the opening of employment opportunities for women in the nineteenth century, as well as part of the general expansion and reform of the professions during this period. These points are discussed in the first chapter, in which comparison with the role of women academics in the United States and continental Europe provides a further context. The second chapter introduces the statistical sample upon which this study is based. Biographical data was collected on women academics at the Oxford and Cambridge women's colleges and selected London colleges at ten-year intervals. This statistical profile reveals the scale and structure of the academic profession for women, and the social origins, education, and career patterns of its members. In the third chapter, the types of provision for women's higher education at the three universities are assessed, in order to help judge how much the academic profession was influenced by the institutional context, and how much by the workings of gender. In the fourth chapter, the early women's colleges are discussed with reference to the founding principals and their influence on the structure and ethos of their colleges. After establishing these contexts, the fifth chapter looks at the establishment of an embryonic academic profession at the women's colleges in the late 1880s. The sixth, seventh, and eighth chapters examine the academic profession for women in the twentieth century. Before the First World War, women academics became more integrated into the male profession as employment opportunities began to appear outside the women's colleges. Women academics also followed the trend towards research, and were gradually admitted to learned societies. The war accelerated the assimilation of women into the profession; the increases in government funding following the war benefited the poverty-stricken women's colleges, enabling them to raise salaries and expand. Women's integration into the profession was not, however, complete. Chapter 8 explores the reaction against women's role in the university during the 1920s. Finally, Chapter 9 gives an assessment of the academic profession for women in 1930. Although there were few actual barriers to women's participation in the profession, academic women remained in a minority for a number of reasons, underlying which was the difficulty of reconciling marriage and career.